Tribochemistry, Mechanical Alloying, Mechanochemistry: What is in a Name? - Michalchuk, Adam A. L.; Boldyreva, Elena V.; Belenguer, Ana M.; Emmerling, Franziska; Boldyrev, Vladimir V. (Frontiers in Chemistry, 2021)
Over the decades, the application of mechanical force to influence chemical reactions has been called by various names: mechanochemistry, tribochemistry, mechanical alloying, to name but a few. The evolution of these terms has largely mirrored the understanding of the field. But what is meant by these terms, why have they evolved, and does it really matter how a process is called? Which parameters should be defined to describe unambiguously the experimental conditions such that others can reproduce the results, or to allow a meaningful comparison between processes explored under different conditions? Can the information on the process be encoded in a clear, concise, and self-explanatory way? We address these questions in this Opinion contribution, which we hope will spark timely and constructive discussion across the international mechanochemistry community.